ChemInform Abstract: Topological Motifs in Cyanometallates: From Building Units to Three‐Periodic Frameworks. Issue 3 (29th December 2015) - Alexandrov, Eugeny V.; Virovets, Alexander V.; Blatov, Vladislav A.; Peresypkina, Eugenia V.
Abstract: Review: 314 refs.